2019
DOI: 10.1371/journal.pone.0223667
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection and genetic characterization of Bartonella species from rodents and their associated ectoparasites from northern Tanzania

Abstract: BackgroundBartonellae are intracellular bacteria, which can cause persistent bacteraemia in humans and a variety of animals. Several rodent-associated Bartonella species are human pathogens but data on their global distribution and epidemiology are limited. The aims of the study were to: 1) determine the prevalence of Bartonella infection in rodents and fleas; 2) identify risk factors for Bartonella infection in rodents; and 3) characterize the Bartonella genotypes present in these rodent and flea populations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 45 publications
0
24
0
1
Order By: Relevance
“…These organisms include Bartonella spp. [ 103 105 ], Coxiella burnetii [ 102 , 106 ], Anaplasma sp. [ 107 ], Theileria sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These organisms include Bartonella spp. [ 103 105 ], Coxiella burnetii [ 102 , 106 ], Anaplasma sp. [ 107 ], Theileria sp.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, among the 53 Bartonella species currently described [ 124 ], more than twenty are associated with rodents. These are the species that usually cause human infections [ 103 ]. We found three different genotypes of Bartonella , which were identified as Bartonella elizabethae from R .…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, PCR sensitivity depends not only on laboratory factors like the choice of PCR primers and Bartonella gene targets, the equipment and methodological considerations, but also on the clinical presentation (illness duration and other factors) and sample type (blood, other body fluid, tissue biopsy, etc.) [ 15 , 16 , 17 ]. With so many factors influencing the accuracy of PCR, a broad range of PCR sensitivity has been reported (33–92%), even when testing solely patients with prototypical diseases caused by Bartonella spp.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, many studies have shown that rodents are important hosts of Bartonella spp. bacteria [ 1 , 5 , 6 ]. More recently, several new species of Bartonella have been isolated in rodents and their ectoparasites in sub-Saharan Africa, including Bartonella mastomydis [ 7 ], Bartonella massiliensis [ 8 ] and Bartonella saheliensis [ 9 ].…”
Section: Introductionmentioning
confidence: 99%